1993
DOI: 10.1111/j.1439-0418.1993.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the nutritional state and the response to aggregation pheromones in the bark beetle, Ips typographus (L.) (Col., Scolytidae)

Abstract: The correlation between nutritional state and behaviour was studied in an overwintering population of bark beetles, Ips typographus (L.). It was found that 3 groups of the bark beetles could be distinguished with respect to their nutrient contents and reactivity to the traps with aggregation pheromone in the field: Group A ‐ newly emerged beetles searching for food ignored the pheromone traps, were shown to have low protein and glycogen contents. Group B ‐ feeding beetles with high lipid and glycogen contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…In the case of a pheromone trap 25 m from an infested tree, only 20-54% of the catch would likely be from the local population (Nemec et al 1993). Based on an analysis of the beetles' fat bodies, Nemec et al (1993) suggested that at most just one-third of the trapped beetles had come from local populations, as their fat bodies were large. The rest of the I. typographus beetles, with more developed muscle tissue, must have flown longer distances.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a pheromone trap 25 m from an infested tree, only 20-54% of the catch would likely be from the local population (Nemec et al 1993). Based on an analysis of the beetles' fat bodies, Nemec et al (1993) suggested that at most just one-third of the trapped beetles had come from local populations, as their fat bodies were large. The rest of the I. typographus beetles, with more developed muscle tissue, must have flown longer distances.…”
Section: Discussionmentioning
confidence: 99%
“…2000)? Do differences exist in the movements of starved and satiated beetles; are there correlations between flight behaviour and nutrient reserves (Nemec et al . 1993)?…”
Section: Discussionmentioning
confidence: 99%
“…Considerable dispersal capability is essential for host location. Some beetles feed and even reproduce in their natal tree before taking their first flight (Byers & Löfqvist, 1989); it is thought that approximately a third of emerging beetles may be attracted by pheromones (if present immediately after emergence, while the remaining two‐thirds travel greater distances and >50% are thought to fly further than 500 m (Nemec, Zumr & Stary, 1993; Wermelinger, 2004). I. typographus can cover distances of >750 m per day, and can probably disperse in excess of 35 km, in extreme cases, crossing areas of unsuitable habitat and high altitude (Botterweg, 1982; Lakatos, 2002; Piel et al , 2005; Stenseth, 1984).…”
Section: Dispersalmentioning
confidence: 99%